AcuD Gene Knockout Attenuates the Virulence of Talaromyces marneffei in a Zebrafish Model. Issue 2 (3rd April 2019) - Feng, Jiao; Chen, Zhiwen; He, Liya; Xiao, Xing; Chen, Chunmei; Chu, Jieming; Mylonakis, Eleftherios; Xi, Liyan
Abstract: Talaromyces marneffei is the only dimorphic species in its genus and causes a fatal systemic mycosis named talaromycosis. Our previous study indicated that knockdown of AcuD gene (encodes isocitrate lyase of glyoxylate bypass) of T. marneffei by RNA interference approach attenuated the virulence of T. marneffei, while the virulence of the AcuD knockout strains was not studied. In this study, T. marneffei -zebrafish infection model was successfully established through hindbrain microinjection with different amounts of T. marneffei yeast cells. After co-incubated at 28°C, the increasing T. marneffei inoculum doses result in greater larval mortality; and hyphae generation might be one virulence factor involved in T. marneffei- zebrafish infection. Moreover, the results demonstrated that the virulence of the ΔAcuD was significantly attenuated in this Zebrafish infection model.